Tanggung Jawab Gereja dalam Melestarikan Lingkungan Hidup di Geosite Sipinsur Desa Pearung Kecamatan Paranginan - Yanti Defi Sianturi; Bestian Simangunsong; Herdiana Boru Hombing; Meditatio Situmorang; Nurelni Limbong (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
Environmental damage is a global phenomenon that demands changes to nature as the common home of all creation. Environmental damage occurs due to excessive human activity. One simple example is the lack of human awareness in terms of disposing of garbage in its place. The purpose of this study was to determine the church's responsibility in preserving the environment at the Sipinsur Geosite. The method in this study was to use a descriptive qualitative method by conducting interviews with several pastors around Sipinsur Tourism and visitors. The data was analyzed to determine the church's responsibility in preserving the environment. The results of the study showed that the church has duties and responsibilities in preserving the environment. The church is not only a place of worship but also a community that embraces in freeing nature from its destruction through (1) Eco-Prophetic Sermons, (2) Waste Management, (3) Tree Planting. Because the environment is God's creation and work. So the church needs to voice criticism or provide input for church members or the government regarding efforts to preserve the environment. This study provides a new contribution to the understanding that the church does not only pay attention to spiritual aspects, but also environmental aspects.